PENGARUH VARIASI MASSA RAGI DAN LAMA FERMENTASI PADA PEMBUATAN BIOETANOL DENGAN BAHAN AMPAS TEBU - Andre Fahrul Rosy; Ena Marlina; Margianto (RING ME, 2024)
The use of ethanol as a fuel is increasing, while the energy source is produced from fossil fuels, namely natural resources that cannot be renewed so that one day the supply will definitely run out. Therefore, bioethanol is needed as a renewable fuel. Bioethanol is a fuel made from plant materials. One of the raw materials for making bioethanol is sugarcane bagasse. This research discusses the effect of variations in yeast mass and fermentation time on the production of bioethanol from sugarcane bagasse using experimental methods. Here the variations in time for fermentation are 2, 4, 6, 8, and 10 days and the mass of yeast is 1 gram, 3 grams, and 6 grams. The results showed that variations in yeast mass of 6 grams for 10 days produced the highest alcohol content (3.5%), while variations in the length of time of the alcohol content test results where the highest value was in variations in the length of 10 days with a total of 6%, it can be concluded that the longer the time fermentation, the alcohol content value will increase. Keywords: Bagasse, Bioethanol, Density, Yield